Indonesian Presidential Election 2019 – Too Close To Call : Whoever Wins, Must Win Decisively - Sebastian, Leonard C. (2019)
Opinion polls and ground feedback show contrasting readings of who is more likely to emerge victorious in this week’s presidential election. Whoever wins must win decisively to avoid a problem of legitimacy.